Analysis Of Pesticide Exposure Can Increase The Risk Of Low Birth Weight Incidence In Agricultural Areas - Damiri, Dini; Bahri, Dinar Auliyatul; Yanti, Nurhalida Indra; Kurniyawan, Enggal Hadi; Kurniawan, Dicky Endrian; Nur, Kholid Rosyidi Muhammad; Afandi, Alfid Tri (Rajaki of Tulip Medika Publisher, 2025)
Pesticide exposure can have various negative impacts on pregnant women, especially for fetal development so that it can cause low birth weight. This study aims to analyze the literature findings over the past five years related to the relevance of pesticide exposure to the incidence of low birth weight in agricultural areas. This research method uses a literature review of 10 selected articles. The databases used were ScienceDirect, Google Scholar, and PubMed, with the keywords pesticides, low birth weight, and agriculture. A total of 10 articles were obtained, and they will go through the screening process through inclusion and exclusion criteria. The results showed that pregnant women in agricultural areas have a greater risk of being exposed to pesticides, which can have an impact on the growth and development of the fetus they are carrying. In addition, it can also cause a decrease in IGF1 levels, which can impact the incidence of LBW. Pregnant women can do prevention by minimizing the use of chemicals containing pesticides and using personal protective equipment. This study found that pesticide exposure can increase the risk of low birth weight incidence in agricultural areas, where most people, especially pregnant women in agricultural areas, feel the negative impact of pesticide exposure on the incidence of low birth weight